(untitled) (Medico Legal Update, 2021)
The aim of the study was to explain the effect of effriction and frirage massage therapy, with a therapy duration of 10 minutes and 15 minutes in helping to reduce movement pain around the injured joint, the injured joint was the ACL ligament which was injured for 1 month and 2 months but pain in the surrounding muscles. ACL at the time of massage therapy was still felt by injured patients. This study was an experiment by providing 2 types of therapy, namely effriction and frirage therapy. Each therapy is a combination of two massage method to get maximum results in reducing pain during flexion and extension of the thigh muscles. With a factorial design with a sample size of 64 people with the criteria to be the sample, namely purposive sampling with injury for 1 month and 2 months. Physical assessment test instruments for pain with an analog visual scale are used to map changes and decreases in pain before treatment and after therapy and changes in range of motion in the knee to support the healing process assisted by these therapeutic method during the effriction massage therapy intervention. Subjective reporting on the level and function of pain is also documented. The results of the study for the homogeneity test mean that the data are homogeneous, and there is a significant difference between the 1 month and 2 month injuries. It was obtained that for massage therapy with an effriction treatment, the duration of the injury was 1 month with a duration of 10 minutes of therapy, which experienced a significant reduction in pain by 0.047 and for effriction therapy with a duration of 15 minutes, it had a significance of 0.049 so that for effriction therapy the duration of the injury was 1 month and for frirage therapy the duration of the injury was 1 month. months with 15 minutes of therapy in this group alone experienced a significant reduction. So that for 1 month there was no interaction between the independent variables and the dependent variable for the duration of 2 months there was an interaction because many factors influenced the reduction of pain and must be described in other studies. Effriction massage therapy is determined as a complementary therapy that is effective in helping to reduce pain relief in knee injuries, especially for 1 month injuries with a duration of 10 minutes and 15 minutes and frirage can significantly reduce pain in the injury duration of 1 month with a therapy duration of 15 minutes, and the type for this therapy there was a non-significant reduction in injury duration of 2 months.